2022
DOI: 10.1002/pits.22771
|View full text |Cite
|
Sign up to set email alerts
|

Network‐related teaching and changes in classroom seating

Abstract: The extent to which teachers make changes in classroom seating reflects, in part, the degree to which they value promoting positive peer relationships in the classroom. We assessed the frequency with which teachers made both minor (i.e., involving only 2–3 students) and major (involving half or more students in the class) changes in classroom seating. We tested whether the frequency of seating changes was linked to teachers' beliefs about promoting positive peer relationships, their attunement to child‐ or pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…At the same time, considering the continuous development of network teaching, teachers should actively carry out learning exchanges among themselves, and network teaching will also get benign growth. The meta-evaluation of the table object proposes the concept of rank bias, so this paper calculates the rank eigenvalues of the research object according to Equation (15) and Equation ( 16), as shown in Table 4. 4 will be analyzed, and it can be seen that the overall evaluation value is between medium and sound and entirely close to good; according to Table 3, it can be seen that the general assessment result is good, which indicates that the development trend is healthy, considering that the audience of network teaching is students, the correlation of students' evaluation is medium.…”
Section: Topologizable Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, considering the continuous development of network teaching, teachers should actively carry out learning exchanges among themselves, and network teaching will also get benign growth. The meta-evaluation of the table object proposes the concept of rank bias, so this paper calculates the rank eigenvalues of the research object according to Equation (15) and Equation ( 16), as shown in Table 4. 4 will be analyzed, and it can be seen that the overall evaluation value is between medium and sound and entirely close to good; according to Table 3, it can be seen that the general assessment result is good, which indicates that the development trend is healthy, considering that the audience of network teaching is students, the correlation of students' evaluation is medium.…”
Section: Topologizable Evaluationmentioning
confidence: 99%
“…With the rapid development of information technology and the popularization of the Internet, distance network teaching has become a hot spot and trend in today's education field. Distance network teaching connects teachers and students through network platforms and tools, realizing the sharing of educational resources and remote collaboration of teaching activities (Steggerda et al, 2023). As an essential part of ideological and moral education in colleges and universities, ideological and political theory courses are also gradually introduced into Cui • Wang • Li distance network teaching (Lv et al, 2022).…”
Section: Introductionmentioning
confidence: 99%